1970
DOI: 10.3329/bjvm.v4i2.1292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of amphistomes in Black Bengal goats in Mymensingh district

Abstract: To investigate the prevalence of amphistome parasites in Black Bengal goats slaughtered at different slaughterhouses of Mymensingh district, a total of 144 gastro-intestinal tracts were examined during the period of July 1998 to June 1999 in the Department of Parasitology, Bangladesh Agricultural University, Mymensingh. Out of 144 Black Bengal goats, 105 (72.92%) were infected with a single or multiple species of amphistomes. In present investigation, three species of amphistomes viz Paramphistomum cervi, Coty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
8
9
1
Order By: Relevance
“…In India, Shahnawaz et al, (2011) identified C. cotylophorum, G. crumenifer and Carmyerius spatiosus in sheep of Kashmir valley. In goats, the present observations were in agreement with other reports of Uddin et al, (2006) and Kabir et al, (2010).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…In India, Shahnawaz et al, (2011) identified C. cotylophorum, G. crumenifer and Carmyerius spatiosus in sheep of Kashmir valley. In goats, the present observations were in agreement with other reports of Uddin et al, (2006) and Kabir et al, (2010).…”
Section: Resultssupporting
confidence: 94%
“…In contrast, the higher prevalence of infection in young sheep was noted by Shahnawaz et al (2011) and Godara et al (2014). The prevalence of infection in goats of more than one year group was reported to be high in the present study by SH examination (63.27%) and this observation was similar to other findings (Uddin et al, 2006;Bunza et al, 2008). The prevalence of infection in this study was reported to apparently higher in female sheep than males (Table 5) and is consistent with Godara et al, (2014).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations